Sentidos do uso de antidepressivos em planos de cuidado em saúde mental no SUS: perspectivas de profissionais da APS - Vasconcelos, José Jardeson Martins (2023)
In 2017, the World Health Organization (WHO) estimated that 300 million people live with depression worldwide, representing an increase of 18% in the period from 2005 to 2015 and making depression the most disabling disease and cause of health problems. of the world. The WHO data is similar to the National Health Survey (PNS) (IBGE, 2020) where it was estimated that 10.2% of people aged 18 or over were diagnosed with depression by a mental health professional in Brazil, representing an amount of 16.3 million people and with the Basic Health Unit being the second most diagnosed place (29.7%). This research sought to understand the meanings of the use of antidepressants within mental health care plans based on the perception of PHC professionals from the SUS. This is a qualitative research study developed with health professionals who make up a Primary Health Care Unit (UAPS) in the city of Fortaleza. The research was carried out by interviewing professionals who make up a Family Health Strategy team, a total of 6 participants (doctor, nurse, dentist, oral health assistant, nursing technician and community health agent). The main results were: the lack of knowledge about antidepressant medication by non-medical professionals and the centrality of care generated by the doctor and the medication, confirming a biological bias in care for people diagnosed with depression; practices aimed at the complementarity of the medicine were initial or with little adherence on the part of professionals; the lack of knowledge of alternatives for mental health care was another important finding of the research; there was also a great emphasis on care generated from the dynamics of spontaneous demand by health professionals, generating greater overload and difficulty in managing mental health demands and depriving the continuity of longitudinal care characteristic of PHC. It is concluded that the demand for depression is the responsibility of the general practitioner, who needs to respond to UAPS users, in an attempt to resolve their demands. However, this practice appears to be limited or incomplete, as it does not provide a resolution to the demand, which in turn adds to the difficulty of non-drug alternatives present in the municipality's psychosocial care network.